2002
DOI: 10.1046/j.1528-1157.2002.49901.x
|View full text |Cite
|
Sign up to set email alerts
|

The Neurodevelopmental Impact of Childhood‐onset Temporal Lobe Epilepsy on Brain Structure and Function

Abstract: Childhood-onset temporal lobe epilepsy appears to be associated with an adverse neurodevelopmental impact on brain structure and cognition that appears generalized in nature and especially evident in white-matter tissue volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
155
0
6

Year Published

2003
2003
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 258 publications
(179 citation statements)
references
References 57 publications
13
155
0
6
Order By: Relevance
“…For example, it used to be thought that recurring febrile seizures were largely harmless, save for episodes of exceedingly prolonged seizures (status epilepticus; SE). However, it has been shown that childhood onset TLE results in reduced brain volumes and cognitive deficits later in life (Hermann et al, 2002). Furthermore, animais subjected to single episodes or a short series of seizures experience cell loss and synaptic rearrangement (Bengzon et al, 1997;Holmes and Ben-Ari, 1998;Haas et al, 2001).…”
Section: Avismentioning
confidence: 99%
“…For example, it used to be thought that recurring febrile seizures were largely harmless, save for episodes of exceedingly prolonged seizures (status epilepticus; SE). However, it has been shown that childhood onset TLE results in reduced brain volumes and cognitive deficits later in life (Hermann et al, 2002). Furthermore, animais subjected to single episodes or a short series of seizures experience cell loss and synaptic rearrangement (Bengzon et al, 1997;Holmes and Ben-Ari, 1998;Haas et al, 2001).…”
Section: Avismentioning
confidence: 99%
“…4 Studies report aberrant face processing mechanisms 5 and gaze direction and emotion recognition deficits. 6,7 Patients often present with broader neurocognitive dysfunction, attributed to a generalized impact of early onset on neurodevelopment, 8 and impairment is often found across different patient groups when compared with healthy controls. Few studies have addressed the link between social perceptual skills and behavioural difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…Estudos com PET têm demonstrado uma diminuição do metabolismo do lobo frontal em pacientes com ELT e os estudos neuropsicológicos mostram um declínio das funções executivas, através do WCST, em pacientes com ELT e depressão (26) . Existem, entretanto, poucos estudos com métodos de neuroimagem mais requintados tentando estabelecer uma correlação entre as alterações observadas na neuroimagem e a presença de transtornos mentais em adultos e crianças com epilepsia.…”
Section: • Estudos De Neuroimagemunclassified